Dr. Rufus B. Weaver and his intriguing dissection of Harriet Cole - Chidinma Nwaogbe; Cameron Schmidt; R. Shane Tubbs (Elsevier, 2018)
Dr. Rufus Benjamin Weaver was a professor of human anatomy at Hahnemann Medical College and a pioneer in the field of anatomy. Among his greatest accomplishments was his complete dissection of the cerebrospinal nervous system. Known as Harriet, the dissection remains displayed at Drexel University College of Medicine and continues to appear in educational materials around the world.